Population genetic characteristics of Hainan medaka with whole-genome resequencing - Yao, Zebin; Long, Shuisheng; Wang, Chun; Huang, Chengqin; Zhang, Hairui; Jian, Liao; Huang, Jingru; Guo, Yusong; Dong, Zhongdian; Wang, Zhongduo (Frontiers in Genetics, 2022)
The DMY gene is deleted in all males of the Sanya population (SY-medaka) of the Hainan medaka, Oryzias curvinotus, as recently reported by us. However, due to limited knowledge regarding their population genetic background, it is difficult to explore the possible evolutionary pathway. Herein, we resequenced the whole genome of four populations, including SY-medaka. A total of 56 mitogenomes and 32,826,105 SNPs were identified. We found that the genetic differentiation is highest between SY-medaka and the other populations. The results of the population history of the O. curvinotus suggest that the SY-medaka has been in a bottleneck period recently. Further analysis shows that SY-medaka are the most strongly affected by environmental selection. Moreover, we screened some potential genomic regions, and the genes contained in these regions may explain the potential mechanism of the selection process of the SY-medaka. In conclusion, our study can provide new clues for the adaptation process of medaka in the new environment of Sanya.